Carbon Nanotubes Redefining the World of Electronics - Kumar Ghosh, Prasanta; Datta, Kunal; Dinkarrao Rushi, Arti (IntechOpen, 2021)
Carbon Nanotubes - Redefining the World of Electronics is a compendium of current, state-of-the-art information about carbon nanotubes (CNTs) and their potential applications in electronics. Chapters cover such topics as the incorporation of CNTs into electronic devices, CNT-based rubber composites for electronic components, the role of CNTs in different energy storage and conversion systems, and ternary implementations of carbon nanotube field-effect transistor (CNTFET) circuits.